Radiological and clinical outcomes of patients diagnosed with intraosseous ganglion cysts of the lunate treated with arthroscopic dorsal ligamento capsulodesis with or without grafting: Minimum 1-year follow-up - Ömer Ayik; Serkan Bayram; Ahmet Emre Paksoy; İsmail Bülent Özçelik (Journal of Orthopaedic Surgery)
Purpose We aimed to compare radiological and clinical results between patients diagnosed with Intraosseous ganglion cysts of the lunate (IGCL)-treated arthroscopic dorsal ligamento capsulodesis (ADLC) with or without grafting. Methods 26 patients who underwent wrist arthroscopy with the diagnosis of intraosseous ganglion cysts of the lunate were included in the study. The patients in the series were divided into two groups according to the surgery they underwent: patients who underwent isolated ADLC in group A and ADLC with autografting in group B. The wrist range of motion, patient satisfaction, Visual Analogue Scale (VAS) and the Mayo Wrist Score (MWS) were used for clinical and functional results. Results Group A consisted of 12 (7 females - 5 males), Group B consisted of 14 (9 females - 5 males). The mean age was 33,1 years in Group A (range 22-49), and 32,3 years in Group B (range 21-47). The VAS, Mayo Wrist Score, wrist range of motion, and the level of patient satisfaction were similar in the two groups. In Group A, the postoperative mean cyst diameter (CD) was 4.2 (range: 1.3 – 7.3 mm), comparable to the mean cyst diameters before surgery. In Group B, trabeculation was observed in 13 patients, and CD was not calculated. Only one patient in Group B had a 3.5 mm (preoperative 3.6 mm) cyst, attributed to graft lysis. Conclusion As we have observed scapholunate instability at different stages in this case series diagnosed with IGCL, we believe that the source of pain is related to instability and treatment should focus on the existing instability. This hypothesis is supported by our obtaining similar results when comparing only ADCLs for instability, which were chosen according to our clinical experience, with those who underwent ADCLs with bone grafting.